Gender-Marked Nicknames Defining a Male Person in English and Russian - Bashirova, Maryam; Konopleva, Natalya; Berezhnaya, Irina (Journal of History Culture and Art Research, 2018)
The object of our research is a group of nicknames –phraseological units that are semantically oriented to a man in Russian and English languages, which includes the nicknames of famous personalities and celebrities, namely politicians, heads of state, athletes, writers and publicists, artists, showmen, oligarchs, as well as historical personalities. Nicknames are active in both social and professional jargons. The nicknames of teachers can be heard only in the speech of schoolchildren of a particular school. The nicknames of politicians, oligarchs sound in the speech of a certain rather closed corporate environment. Despite this, this language platform has become widely used both in the pages of the periodical press and on numerous Internet sites. Firstly, the article presents a theoretical review of the literature. Then authors offer their own classification of nicknames, which includes 12 nominations. On the basis of which a comparative analysis of these nicknames is carried out.